The Effect of Fraud Hexagon and Earnings Management on Financial Statement Fraud in Pharmaceutical and Cosmetic Companies Listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 Period - Anggraeni, Annisa Fitri; Fairuz, Sena (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
This study aims to analyze the effect of Fraud Hexagon and Earnings Management on Financial Statement Fraud in pharmaceutical and beauty sector companies listed on the Indonesia Stock Exchange for the 2022–2024 period. Fraud Hexagon consists of six variables, namely stimulus, capability, opportunity, rationalization, arrogancy, and collusion. In this study, stimulus is proxied by financial targets, capability is proxied by changes in directors, opportunity is proxied by nature of industry, rationalization is proxied by auditor changes, arrogancy is proxied by calculating the number of CEO pictures, and collusion is proxied by cooperation with the government, while Earnings Management uses the Jones model. The sampling technique used is purposive sampling, resulting in 14 companies as the research sample. The data analysis method used in this study is logistic regression analysis using IBM SPSS 26 software. The results show that the variables financial targets, changes in directors, auditor changes, the number of CEO pictures, and cooperation with the government do not affect financial statement fraud, while nature of industry and Earnings Management have a positive effect on financial statement fraud. Based on these results, it can be concluded that only nature of industry and Earnings Management influence the tendency of financial statement fraud, while the other variables do not show any effect. Future research is recommended to expand the research object, add other variables related to financial statement fraud, and use other detection methods such as the F-Score.